2020
DOI: 10.3390/ijerph17093311
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Imported Cases of COVID-19 in Taiwan: A Nationwide Study

Abstract: In the early stages of the 2019 novel coronavirus disease (COVID-19) pandemic, containment of disease importation from epidemic areas was essential for outbreak control. This study is based on publicly accessible data on confirmed COVID-19 cases in Taiwan extracted from the Taiwan Centers for Disease Control website. We analysed the characteristics, infection source, symptom presentation, and route of identification of the 321 imported cases that were identified from 21 January to 6 April 2020. They were mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 18 publications
0
84
2
Order By: Relevance
“…It is well established that optimising caloric and protein intake is important to support recovery of functional muscle mass. The post-ICU COVID-19 survivor will face commonly reported problems with nutrition (e.g., loss of appetite, swallowing disorders) and the additional symptom of loss of taste (ageusia) and smell (anosmia) are now recognised symptom of COVID-19 (37). In general, for those with chronic respiratory disease weight loss and wasting of muscle and bone tissue may be induced or accelerated during severe acute exacerbations of respiratory disease requiring hospitalisation, due to the combination of malnutrition, physical inactivity, hypoxia, systemic inflammation and/or systemic glucocorticoids (38), this is likely to be mirrored in the COVID patient.…”
Section: The International Task Force Suggests That Covid-19 Survivormentioning
confidence: 99%
“…It is well established that optimising caloric and protein intake is important to support recovery of functional muscle mass. The post-ICU COVID-19 survivor will face commonly reported problems with nutrition (e.g., loss of appetite, swallowing disorders) and the additional symptom of loss of taste (ageusia) and smell (anosmia) are now recognised symptom of COVID-19 (37). In general, for those with chronic respiratory disease weight loss and wasting of muscle and bone tissue may be induced or accelerated during severe acute exacerbations of respiratory disease requiring hospitalisation, due to the combination of malnutrition, physical inactivity, hypoxia, systemic inflammation and/or systemic glucocorticoids (38), this is likely to be mirrored in the COVID patient.…”
Section: The International Task Force Suggests That Covid-19 Survivormentioning
confidence: 99%
“…The estimated prevalence of COVID-19 in the 13 studies ranged from 7.96% by Lee et al 17 to 75.74% Yan et al 31 The estimated pooled prevalence of combined loss of smell and taste in COVID-19 patients was 35.04% (95% CI, 22.03%-49.26%). Both loss of smell and taste were reported in 5 publications each from Asia 7,17,20,23,45 and Europe 5,27,40,48,49 and 3 from North America. 8,9,31 The estimated pooled prevalence of loss of smell and taste in the populations of Europe, North America, and Asia regions was 31.26% (95% CI, 13.64%-52.22%), 66.84% (95% CI, 56.18%-76.70%), and 15.89% (95% CI, 8.15%-25.42%), respectively (Figure 4).…”
Section: Prevalence Of Loss Of Smell And/or Taste In Covid-19 Patientsmentioning
confidence: 99%
“…Several studies from the United States, China, South Korea, Iran, Australia, France, Spain, Italy, United Kingdom, and Germany strongly confirmed different degrees of loss of smell (anosmia/hyposmia/dysosmia) and loss of taste (ageusia/hypogeusia/dysgeusia) as early symptoms of COVID-19. 4 - 32 It was observed that sudden loss in smell and taste could be the only features in asymptomatic newly infected individuals and could also serve as early symptoms of the disease. In fact, the American Academy of Otolaryngology–Head and Neck Surgery Foundation and Ear, Nose, and Throat Society of the United Kingdom (ENTUK) recommended that patients presenting with these clinical features should commence self-isolation before alerting the health authorities.…”
mentioning
confidence: 99%
“…6 A study of 321 imported COVID-19 cases to Taiwan revealed only 44.9% had fever, three-quarters of had respiratory symptoms, 13.1% had loss of smell or taste, and 7.2% had diarrhea. 11 This signifies that body temperature screening at the ED door does not ensure detection of all cases and can miss those without obvious symptoms. A graded approach in testing allows testing of even low-risk patients, who may not have been eligible for testing.…”
Section: Discussionmentioning
confidence: 99%